Case report: Successful perioperative intervention with efgartigimod in a patient in myasthenic crisis - Shelly, Shahar (Frontiers in Immunology, 2025)
IntroductionThis case describes successful response to efgartigimod in the treatment of myasthenic crisis secondary to paraneoplastic disease, and in the perioperative setting.MethodsAn elderly female presented with speech difficulties, cessation of eating and 10kg weight loss over 4 months.ResultsExamination revealed ptosis, dysarthria, nasal speech, and weakness in limbs and neck flexors. Single fiber electromyography demonstrated abnormal jitter response in the orbicularis oculi muscle. Nicotinic acetylcholine receptor antibodies were detected in serum. The patient was diagnosed with very-late-onset myasthenia gravis (MG) in a myasthenic crisis and later required intubation and admission to intensive care but was unresponsive to plasma exchange. Paraneoplastic disease was suspected and computed tomography revealed a bladder mass. Efgartigimod 10 mg/kg was administered intravenously to stabilize her condition before surgery. The patient’s Myasthenia Gravis Activities of Daily Living (MG-ADL) score decreased from 19 to 14 after the first dose and she subsequently underwent surgical removal of the bladder tumor without complication. Her condition continued to improve post-operatively with completion of the first treatment cycle. Four cycles of efgartigimod over 10 months resulted in an MG-ADL score of 3.DiscussionEfgartigimod may be a novel treatment for perioperative management of MG, myasthenic crisis, and paraneoplastic MG. Further study is warranted.